Oppression on black women in Bernardine Evaristo’s Girl, Woman, Other - Herika Herika; Danu Wahyono (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2023)
The article is about Oppression on Black Women in Bernardine Evaristo’s Girl, Woman, Other. The problems are: (1) How is the oppression on black women representation in Bernardine Evaristo Girl, Woman Other? (2) What are the causes of oppression on black women in Bernardine Evaristo Girl, Woman, Other? (3) What are the effects of oppression on black women in Bernardine Evaristo Girl, Woman, Other? The objective of the study is to find reflection of oppression on black women and the cause and the effect of the oppression. In analysis the problem, the thesis writer applies a qualitative method. The thesis writer uses extrinsic approach and psychological approach. The analysis shows that black women experience oppression. The forms of oppression found were discrimination, sexual harassment, racism, verbal abuse, violence, exploitation, and powerlessness. Several causes that make black women experience oppression such as patriarchy, social status, and lack of resources make them experience oppression. The effects of oppression largely determine a women's reaction after experiencing bullying. Some of the effects of oppression are the first household that can be seen. Women take care of all household chores and serve their husbands, because position for men that is higher than women. The second is taking care of children. A woman changes perceptions and as a mother who always protects her children from oppression that ensures happiness of her children. From this analysis it can be concluded that oppression occurs when there is group power to become oppressors, there are causes of oppression so that it has an effect on someone after experiencing oppression.